Light‐Fuelled Self‐Assembly of Cyclic Peptides into Supramolecular Tubules. Issue 6 (4th May 2020) - Cissé, Nicolas; Kudernac, Tibor
Abstract: The work performed by supramolecular polymers, such as microtubules and actin filaments, supports the life of the cell, and essentially involves fuel‐driven self‐assembly pathways. Developing fuel‐driven supramolecular polymerization processes is therefore crucial to the realization of mechanically active molecular systems. Here, we demonstrate supramolecular tubules with non‐equilibrium steady states that are fuelled by light. This dynamic supramolecular system features rapid cycles of self‐assembly and disassembly, at rates that appear fast enough to perform mechanical tasks in fluids effectively. Abstract : The self‐assembly of cyclic peptides into supramolecular tubules is fuelled by light via the photoacid‐mediated protonation of carboxylic acid residues. Light intensity is used to control the speed of the assembly and disassembly processes, as well as as a means to access specific self‐assembled states. This supramolecular system operates continuously and repeatedly, without any waste, and demonstrates a dynamic behaviour that is key to the operation of artificial polymerization machines.